Items Analysis of Midterm Exam Test on Difficulty Level and Discrimination Index Based on Bloom Taxonomy: A Case of Junior High School Mathematics Problems - Kholifah, Nur; Suhendarti, Mamik; Liberna, Hawa (Jurnal Pendidikan MIPA, 2022)
The purpose of this study was to find out how the level of difficulty on the Middle Semester Assessment of Mathematics class VII SMP Negeri 5 Cibitung for the 2021/2022 academic year was based on Bloom's taxonomy. This research was conducted at SMP Negeri 5 Cibitung. The type of research is descriptive research with a quantitative approach. The data collection technique used is the documentation method, while the data analysis technique uses Microsoft Excel with formulas to test validity, reliability, difficulty level, discriminatory power, and calculate the percentage level of difficulty of questions based on Bloom's taxonomy. Based on the results of the analysis, it can be concluded that there are 18 items (90%) which are declared valid, and the items are declared reliable with a reliability coefficient of 0.83. The results of the analysis of questions based on Bloom's taxonomy, obtained questions belonging to the ability to understand (C2) as many as 5 items (25%), belonging to the ability to apply (C3) as many as 10 items (50%), and belonging to the ability to analyze (C4) as many as 5 items (25%). There are no questions belonging to the ability to remember (C1), evaluate (C5), and create (C6), then the questions are classified based on the students' thinking criteria, and the questions that are classified as Higher Order Thinking Skills (HOTS) are 5 items (25%) and questions that are classified as Medium Order Thinking Skills (MOTS) as many as 15 items (75%). Keywords: difficulty level, mid-semester assessment, Bloom's taxonomy. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp486-495